Efficacy of Credit Risk Management on The Performance of Banks in Nigeria A Study of Union Bank PLC (2006-2010) (Global Journal of Management and Business Research, 2013)
Adequately managing credit risk in financial institutions is critical for the survival and growth of the Financial Institutions. The study aimed at assessing the efficacy of credit risk management on banks performance. Also to determine if credit risk have effect on the profitability and examining the relationship between interest income and bad debt of the Union Bank. Secondary sources of data were used for the study. Time series and trend analysis are used for the analysis. Correlation coefficient and regression analysis were used in testing the hypotheses. The study conclude that credit risk affect the performance of Union Bank PLC and that to maintain high interest income, attention needs to be given to credit risk management especially regarding the lending philosophy of Union Bank. The study recommends that union bank PLC should ensure that loans given out to customers should be adequately reviewed from time to time to assess the level of its risk such loan should be backed by collateral security.
Keywords: credit; risk; performance; management